Kesesuaian Higher Order Thinking Skill pada Instrumen Evaluasi Buku Ajar Pendidikan Pancasila di Perguruan Tinggi - Zulvarina, Prima; Saraswati, Destriana; Fiaji, Noveria Anggraeni (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study described the diversity of higher order thinking skills in the evaluation instrument for Pancasila Education textbooks in universities and analyzed the level of conformity of higher order thinking skills in the evaluation instrument for Pancasila Education textbooks in universities. This study used a qualitative approach with the type of descriptive research. Data were collected utilizing observation and document study. The data obtained were analyzed by descriptive, interpretive techniques through data reduction, data presentation, and verification. The study results indicated that the evaluation instrument in the Pancasila Education textbook contained all the criteria for higher-order thinking skills, including critical thinking, problem-solving, decision-making, and creative thinking. However, the evaluation instrument in the Pancasila Education textbook, which contained criteria for higher-order thinking skills, was only 36 out of 78 items. Therefore, the Pancasila Education textbook needed to be revised again because the number of analyzing levels was more dominant than evaluating and creating. In addition, the cognitive domain in the Pancasila Education textbook was out of tune with the National Higher Education Standards guidelines.